Oscar Alvin Danielson papers - Danielson, Oscar Alvin
Correspondence, financial records, printed matter, annotated sketches, blueprints, illustrated material, and a photograph chiefly documenting Danielson's interest in the development of airplanes and their instrumentation. Includes international patent applications for a speedometer. Correspondents include the Aero Club of America and the Wright Company.
Inventor and aviator.
Collection material in English, with French.
Keywords: Aero Club of America -- Correspondence; Wright Company -- Correspondence; Aeronautics; Airplanes; Patents; Speedometers; Aviators; Inventors